2018
DOI: 10.1177/1045389x18781047
|View full text |Cite
|
Sign up to set email alerts
|

Experimental validation of shape memory material model implemented in commercial finite element software under multiaxial loading

Abstract: Shape memory alloys are used in ever-increasing numbers of applications, such as implants made of porous shape memory alloys, where the material is subjected to complex loading conditions with various loading paths. Finite element simulation of such parts requires utilizing a constitutive model that is able to capture the multiaxial and path-dependent behavior of shape memory alloys. The main objective of this article is to investigate the accuracy of the constitutive model implemented in current commercial fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…When the ratio is less than 0.71, the material exhibits cyclic hardening behavior [55]. According to the experimental result [36] (figure 3(c)), the yield ratio of LPBF-processed NiTi was 0.585 (<0.71), which meant that cyclic hardening behavior occurred during compression tests. Figures 9(b), (d), (f) and (h) show the recovery strain after unloading (ε unload , marked by green), the recovery strain via heating (ε heat , marked by red), and irrecoverable strain (ε irr , marked by blue).…”
Section: Analysis Of Smementioning
confidence: 91%
See 1 more Smart Citation
“…When the ratio is less than 0.71, the material exhibits cyclic hardening behavior [55]. According to the experimental result [36] (figure 3(c)), the yield ratio of LPBF-processed NiTi was 0.585 (<0.71), which meant that cyclic hardening behavior occurred during compression tests. Figures 9(b), (d), (f) and (h) show the recovery strain after unloading (ε unload , marked by green), the recovery strain via heating (ε heat , marked by red), and irrecoverable strain (ε irr , marked by blue).…”
Section: Analysis Of Smementioning
confidence: 91%
“…The numerical simulation of components was conducted to analyze the stress distribution and deformation process of bionic lattice structures. According to the stress-strain curve of the NiTi sample [36] (figure 3(c)), material properties of NiTi were set as shown in table 2. Before using the data, the chemical composition and tensile properties of NiTi materials were compared to ensure that the error was within the allowable range.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Recently, the use of shape memory alloy (SMA) materials has been significantly increasing due to their unique properties such as adapting intelligently to external disturbances (Khodaei and Terriault, 2018; Kuo et al, 2012; Liu et al, 2020; Sohn et al, 2018; Vignoli et al, 2020). An SMA is categorized as a smart material capable of changing its crystal structure between the martensite phase and the austenite phase through thermo-mechanical loading.…”
Section: Introductionmentioning
confidence: 99%
“…Among most multiaxial studies mentioned above, the transformation behavior and the material degradation were examined only at the macroscopic length scale. Khodaei et al showed that constitutive modelling failed to predict the mechanical response under multiaxial loads, because the model does not capture the anisotropic transformation behaviour related to the crystallographic orientation and the loading path [33]. Detailed experimental data is required to improve the micromechanical models.…”
Section: Introductionmentioning
confidence: 99%